Analysis of Atrial Fibrillation Treatment Regimes in a Multicenter Cohort of Transcatheter Edge-to-Edge Mitral Valve Repair Patients - Christian Waechter; Felix Ausbuettel; Georgios Chatzis; Dieter Fischer; Holger Nef; Sebastian Barth; Philipp Halbfaß; Thomas Deneke; Sebastian Kerber; Dimitar Divchev; Bernhard Schieffer; Ulrich Luesebrink (Journal of Interventional Cardiology)
Background. Atrial fibrillation (AF) is a highly prevalent comorbidity in patients with severe mitral valve regurgitation (MR). Recent studies show a deleterious outcome of patients with concomitant AF after transcatheter mitral valve repair (TMVR). This underlines the essential need for additional strategies that ameliorate the prognosis of these patients. Fundamental data on AF characteristics and treatment regimes in this special cohort of patients are lacking. Methods. We retrospectively analyzed the data of 542 consecutive patients with severe MR undergoing TMVR in three tertiary heart centers with special focus on AF type and underlying treatment strategies. Results. The prevalence of concomitant AF was 73.3%, and AF did not affect the procedural success or the incidence of major adverse cardiac and cerebrovascular events. The patients with AF were more frequently >75 years, had more tricuspid regurgitation, and less coronary artery disease than non-AF patients. The distribution of AF types was 32% paroxysmal AF, 27% persistent AF, and 41% permanent AF. Except for a higher degree in severe tricuspid regurgitation and a higher likelihood of male sex, no substantial differences were observed while comparing permanent and nonpermanent AF patients. The predominant treatment regime was rate control (57%), with only beta blockers (BB) in the majority of persistent and permanent AF patients, while additional digitalis or a pacemaker was used infrequently. Rhythm control was mainly achieved with BB alone in paroxysmal AF patients and with additional antiarrhythmic drugs in the majority of persistent AF patients. Interventional rhythm control therapy was performed in 2.5% and 30.9% of paroxysmal and persistent AF patients, respectively. The guideline-adherent use of oral anticoagulants was comparable and high in both groups (91.9% in nonpermanent vs. 90.1% in permanent AF). Conclusion. This is the first study to provide necessary information for the understanding of the current clinical practice in dealing with TMVR patients. Since evidence suggests that AF is not a benign concomitant disease, further investigations are needed to assess the prognostic impact of these different AF treatment strategies.